The problem of social workers in kindergarten It is a field research in Sulaimani - Saleh, L. Avan Fouad Faqi; Abdullah, L. Nechirvan Anwar (Sulaimani Journal for Humanities, 2026)
The main objective of this study is to understand the problems of social workers in kindergartens and focuses on the social and psychological problems of social workers in kindergartens, including the problem of “professional identity” of researchers in general. The research community included public and non-governmental kindergartens in Sulaimani, where 12 social workers were included as a sample of research. After presenting the interviews, the results show that the researchers generally have problems of social incompatibility with children's families and kindergarten administrative staff, while psychologically experiencing a lot of stress, burnout and boredom because they are given other tasks. Regarding the issue of professional identity, they consider it more appropriate to have their professional title (educational counselor), because researchers work in the education sector and consider this title more appropriate than (social researcher).
Keywords: problem; social worker; child; kindergarten